Peranan Pemilihan Strategi dan Stilistika pada Iklan di Televisi - Mezia Kemala Sari (Rekam: Jurnal Fotografi, Televisi, Animasi)
Television is one of the best medium today that can connect producers’goals with consumers' needs. The televisions’ impressions are crucial so that consumers can easily get new things through the television’s impressions like advertisment.Advertisment becomes very important when producer wants to offer product or service. It can be easily achieved by making advertisment on television to get potential buyers’attention.The main goal is to deliver advertising messages by using attractive packaged to stimulate consumers. The things that should be considerated in choosing strategies are the relevancies to product itself, competitors and also clear target market. Advertisement should pay attention to the Stylistics’ advertising aspects. In getting the uniqueness of style, producers can use language strategies usage like slogans, selection of interesting characters, selection of appropriate strategies and also using other advertising elements. The selection advertisements’ strategies will determine conveying stylistics’ messages through form of creativity to get the better consumerresponse.